Pesantren and The Potency of Creative Economics - Uula, Mimma Maripatul (The Economic Review of Pesantren, 2024)
This study aims to see the development of research on the topic of "Pesantren and Creative Economic" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Pesantren and Creative Economic" which comes from the Dimension database with a total of 44 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of research development "Pesantren and Creative Economic" in the world. The results of the study found that there were 5 clusters with the most used words being school, student, activity, program, field, economy, and trainin. Then, the topics of research paths related to Pesantren and Creative Economic are Creative Economic Innovation in Pesantren, Pesantren support halal tourism, Creative leadership style in pesantren, The role of Kyai in Pesantren Economic, and Creative product development by santri.